Efek antidiabetes minuman GEMAR (Germinated Black Rice) pada tikus model diabetes melitus - Pasaribu, Sudana Fatahillah; Chandra, Putra; Irwanto, Reno; Anggraini, Citra Dewi; Herviana, Herviana (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Type 2 diabetes mellitus (T2DM) is a degenerative disease caused by increased blood glucose levels. Therapeutic recommendations for treating T2DM are the implementation of healthy lifestyle and pharmacological interventions. Germinated Black Rice contain high levels of fiber, anthocyanins and flavonoids. Functional beverage products Germinated Black Rice (GEMAR) is expected to help improve blood glucose levels and body weight in T2DM sufferers. This study aims to analyze the effect of beverage GEMAR at doses of 3.8 and 7.6 g/200 gBW on fasting blood glucose and body weight in T2DM rats. Laboratory experimental research method with design pre-posttest control group design. Samples of 30 male Wistar rats were divided into 5 groups. The results of the study found that the fasting blood glucose (GDP) of the acarbose drug group, P1 (GEMAR 3.8 g/200 g BW) and P2 (GEMAR 7.6 g/200 g BW) were significantly different (p<0.001) compared to the negative control group. GDP reducing effect of acarbose drug treatment (148%), P1 (177%), and P2 (128%). Body weight in the acarbose, P1 and P2 drug groups were significantly different (p<0.001) compared to the negative control. The improved effect of the drug groups acarbose (4%), P1 (7%), and P2 (5%) compared with adaptation. This research concludes that GEMAR P1 and P2 functional beverage can reduce GDP levels and improve body weight T2DM rats.